New insights on the importance of real-time marketing on building brand engagement and brand equity - Pereira, Teresa Viana (2020)
User participation has been gaining more importance on the Web. Customers are now creators and engagers of content, through multiple platforms such as Social Media. Through User-Generated Content, they create content and are instigated to like, comment and share some posts. Recognizing the importance of social networks, many brands have become present in these platforms as a way of keeping closer relationships with the consumers, establishing, developing, maintaining and improving such relationships – Relationship Marketing – and building Brand Equity. Brand Communities have also come online, being more accessible worldwide – Online Brand Communities. Sometimes its members are given the chance to Co-create with the brands strengthening the community and the interactions between them, ultimately increasing Brand Engagement. This dissertation investigates Real-Time Marketing as one strategy for businesses to take advantage of this social and technological ecosystem. The challenge of a more social and connected consumer is that they engage in online conversations, trends and things happening today. To get into those conversations, brands can launch campaigns and lay their communication strategy on events of public interest, relating their messages with a context. The model proposed revealed a good fit and proved the antecedent role of Co-creation on the Social Media Context, which will therefore positively impact User-Generated Content which will positively impact Brand Equity and Engagement. This study proves that Real-Time marketing leads to situations of increased User-Generated Content, complementing previous findings and addresses the gap in literature proving that Real-Time marketing leads to situations of increased Brand Equity and Brand Engagement.